2010
DOI: 10.1007/s10554-010-9672-6
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and dimensions of the pulmonary artery bifurcation in children and adolescents: assessment in vivo by contrast-enhanced MR-angiography

Abstract: We sought to establish normal values for the diameters of the main (MPA), right (RPA), and left (LPA) pulmonary arteries and for the angles describing the geometry of the pulmonary artery bifurcation in children by using contrast-enhanced magnetic resonance angiography (CE-MRA). CE-MRA was performed in 69 children without cardiovascular disease. The median age was 10 ± 4.9 years (range 2-20), weight 37.4 ± 18.5 kg (10-82), body surface area (BSA) 1.18 ± 0.4 m(2) (0.48-2.07). The pulmonary artery diameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 23 publications
5
70
1
Order By: Relevance
“…13 Aortic measurements were obtained at the following 5 levels (Figure 1): neoaortic root, mid-AAo, distal transverse arch, isthmus, and descending aorta at the level of the diaphragm. Each aortic segment was reformatted in a double oblique plane, and 2 orthogonal measurements were recorded at each level as described by Kaiser et al 14 The aortic root was measured from sinus-to-commissure in one dimension (labeled as anteroposterior [AP]) and cusp-to-cusp in the other (labeled as lateral dimension) according to the method of Burman et al 15 The pulmonary arteries were similarly measured as described by Knobel et al 16 Body surface area (BSA) at the time of CMR was calculated from the patient height and weight using the method of Haycock et al 17 Volumetric measurements were adjusted to BSA 1.3 , and linear measurements were indexed to BSA 0.5 . 18-20 z scores were calculated from published normal values.…”
Section: Cmr Measurementsmentioning
confidence: 99%
“…13 Aortic measurements were obtained at the following 5 levels (Figure 1): neoaortic root, mid-AAo, distal transverse arch, isthmus, and descending aorta at the level of the diaphragm. Each aortic segment was reformatted in a double oblique plane, and 2 orthogonal measurements were recorded at each level as described by Kaiser et al 14 The aortic root was measured from sinus-to-commissure in one dimension (labeled as anteroposterior [AP]) and cusp-to-cusp in the other (labeled as lateral dimension) according to the method of Burman et al 15 The pulmonary arteries were similarly measured as described by Knobel et al 16 Body surface area (BSA) at the time of CMR was calculated from the patient height and weight using the method of Haycock et al 17 Volumetric measurements were adjusted to BSA 1.3 , and linear measurements were indexed to BSA 0.5 . 18-20 z scores were calculated from published normal values.…”
Section: Cmr Measurementsmentioning
confidence: 99%
“…Normal values for the geometry and dimensions of the pulmonary artery bifurcation were established by contrast-enhanced MRA [60]. Prompona et al [61] found MRI to be useful for evaluating sinus venosus atrial septal defects and anomalous pulmonary venous drainage.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…[1][2][3][4][5][6] Gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA), which has a low molecular weight, is the¯rst MRI contrast agent approved by the United States Food and Drug Administration (FDA) since 1988. Magnetic resonance imaging (MRI) is a powerful modality for lesion detection, because it shows a high contrast between tissues and has the advantage of no ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%